2005
DOI: 10.1111/j.0742-2822.2005.03108.x
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Mitral Valve Repair: Predictive Significance of Restrictive Left Ventricular Diastolic Filling

Abstract: In patients with severe LV dysfunction undergoing combined CABG and MV repair, restrictive LV diastolic filling pattern is an important preoperative marker of high perioperative mortality rate, further negative remodeling of LV, and progression of mitral regurgitation late after MV repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Previous studies [23, 77,85,86,87,88,89] identified the preoperative predictors of MVA failure as larger LV diameter, sphericity index, mitral annulus diameter, mitral valve tenting area and MR severity (table 3). In a recent study from our group [23], a mitral valve tenting area ≥2.5 cm 2 , a coaptation distance ≥1 cm and a posterior leaflet angle ≥45° measured by TTE had a good sensitivity and specificity to predict persistent MR following MVA (table 3).…”
Section: Treatment Of Ischemic Mrmentioning
confidence: 99%
“…Previous studies [23, 77,85,86,87,88,89] identified the preoperative predictors of MVA failure as larger LV diameter, sphericity index, mitral annulus diameter, mitral valve tenting area and MR severity (table 3). In a recent study from our group [23], a mitral valve tenting area ≥2.5 cm 2 , a coaptation distance ≥1 cm and a posterior leaflet angle ≥45° measured by TTE had a good sensitivity and specificity to predict persistent MR following MVA (table 3).…”
Section: Treatment Of Ischemic Mrmentioning
confidence: 99%
“…These latter studies only included general cardiac or coronary artery surgery (CAS) patients. It is unknown if similar superiority also applies to patients after valvular surgery (VS) expected to have a diminished left ventricular systolic and diastolic function after surgery, following chronic volume or pressure overload [2,6,[20][21][22][23]. Whereas La Place's law describes that ventricular radius and thus volume interacts with filling pressure to reflect ventricular preload, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2. Kongsaerepong et al 30 analyzed the records of 365 patients who underwent CABG + UMRA and found these independent predictors for RIMR: 1. Annular diameter, 2.…”
Section: Persistent and Recurrent Mitral Regurgitationmentioning
confidence: 99%
“…Regurgitation degree. Patients with mitral annular diameter ≥ 3.7 cm with a tenting area of ≥ 1.6 cm 2 in long axis view and an IMR grade > 3.5 have a 50% probability of regurgitation recurrence during follow-up 30 . Hung et al 29 reported that recurrence of IMR after ring annuloplasty is due to progression of ventricular remodelling as shown by increase in LV volume and sphericity index.…”
Section: Persistent and Recurrent Mitral Regurgitationmentioning
confidence: 99%
See 1 more Smart Citation